Green and more sustainable catalyst for CO and CO2 hydrogenation - Masoud Safari Yazd; Jafar Towfighi Darian (Energy Conversion and Management: X)
This study presents a comprehensive approach to fabricating eco-friendly cobalt-based nano-catalyst using okra mucilage as a natural encapsulating and stabilizing agent for CO and CO2 hydrogenation. Two distinct fabrication routes are evaluated: one utilizing Zeolitic Imidazolate Framework-67 (ZIF-67) stabilized cobalt nanoparticles (NPs) encapsulated by silica (NC catalyst), and the other employing okra mucilage (GNC catalyst). The ZIF-67 route with modified silica encapsulation shows enhanced thermal stability and mass transfer capabilities, essential for Fischer-Tropsch Synthesis (FTS). In contrast, okra mucilage offers a greener and more economical alternative, forming a higher surface area catalyst with better pore accessibility. The green nano-catalyst derived from okra mucilage exhibited superior reduction behavior, thermal stability up to 600 °C, and enhanced dispersion of active sites, which influence catalyst performance. Additionally, the crucial role of H2/CO/CO2 adsorption on the catalysts’ performance is evaluated experimentally through H2/CO/CO2-TPD and theoretically by employing molecular dynamics. Although the NC catalyst demonstrates superior CO and CO2 conversion due to higher H2 uptake, its performance declines more rapidly over time compared to the GNC catalyst, which has superior durability. Furthermore, the GNC catalyst presents improved selectivity for liquid fuel production due to its higher CO and CO2 uptake than the NC catalyst. These findings highlight the potential of okra mucilage as a sustainable, cost-effective sacrificial template for green catalyst fabrication, with the GNC catalyst offering environmental benefits, enhanced stability, and selectivity in FTS, making it a promising candidate for sustainable catalyst development.